Citra Media Massa Dimata Masyarakat Palembang Studi: Branding Media Palembang Ekspres (Palpres) - Puspa Maryuni; Sumaina Duku; Silvia Assoboru (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to determine the image of the Palembang Ekspres (Palpres) mass media in the eyes of the Palembang community through an analysis of the media branding strategies implemented and the public's assessment of the media's image. This study uses a mixed methods method with an exploratory sequential design, namely qualitative data analysis is carried out first to explore the branding strategies implemented, then used as a basis for compiling quantitative instruments to measure public assessments of the media's image. Qualitative data are obtained through in-depth interviews with internal parties of Palembang Ekspres, while quantitative data are obtained through distributing questionnaires to 100 respondents from the Palembang community who have accessed Palpres news, using a purposive sampling technique. Qualitative data analysis in this study is carried out through a process of reduction, data compilation, and drawing conclusions. Meanwhile, quantitative data were analyzed using descriptive statistics and then followed by a simple linear regression test to examine the relationship between variables. The results showed that Palembang Ekspres implemented five main elements in its branding strategy: brand identity, brand positioning, brand communication, brand experience, and brand personality. The implementation of this strategy was evident through the consistency of its visual identity, the presentation of fast and relevant news, the utilization of various digital platforms such as Instagram, Facebook, YouTube, and TikTok, and the use of visual content to enhance the reader experience. Quantitative findings indicated that Palpres' image was in the positive category, particularly in terms of credibility, information quality, news clarity, and public trust. The regression test also showed that the branding strategy had a significant influence on Palpres' image in the eyes of the Palembang community. Thus, this study confirms that the branding strategy implemented by Palembang Ekspres was able to create a positive image among the Palembang community.